Penerapan Model Project Based Learning (PBJL) Berbantuan Mind Map terhadap Keaktifan dan Hasil Belajar Peserta Didik Kelas IV SDN 106161 Laut Dendang - Feby Nisha Bintang; Jelita Damai Haloho; Refi Yulina Nasution; Tabita Theresia (International Forum of Researchers and Lecturers, 2024)
Activeness and Learning Results of Class IV Students at SDN 106161 Laut Dendang Assisted by the PBJL Project Based Learning Model. The aim of this research is to increase student learning activity and achievement through the use of a project-based learning model supported by mind maps as a medium. This research is PTK, and the subjects are fourth grade students. Data is collected using test scores, observation results, and activity rubrics. Quantitative and qualitative descriptive methods were used to analyze the data. The results showed that students who were inactive at the beginning of the cycle (64.70%) increased to 76.47%, 26 were quite active, and 24 students who were active increased to 82.35%. For pre-cycle learning outcomes, grade 4 students at SDN Laut Dendang showed completeness of 4.4% 14 students, increasing to 5.9% 20 students, and 85% 29 students in cycle II. Thus, implementing project-based learning with the help of mind maps can increase student activity and learning outcomes.